Excimer laser coronary atherectomy in severely calcified lesions: time to bust the myth - Lucía Cobarro; Alfonso Jurado-Román; Daniel Tébar-Márquez; Silvio Vera-Vera; Artemio García-Escobar; Clara Ugueto; Cristina Contreras; Borja Rivero; Santiago Jiménez-Valero; Guillermo Galeote; Raúl Moreno (REC: Interventional Cardiology (English Ed.), 2024)
ABSTRACT Introduction and objectives: No previous studies have established the contemporary use and outcomes of Excimer laser coronary atherectomy (ELCA) in percutaneous coronary intervention (PCI) of severely calcified coronary lesions. The aim of this study was to assess the safety, efficacy, and 1-year outcomes of ELCA in this setting. Methods: We retrospectively examined the clinical and angiographic characteristics and procedural outcomes of severely calcified lesions treated with ELCA-assisted PCI in our institution between 2016 and 2022. Results: Seventy-eight consecutive patients (80 procedures) were included (mean age 71.2 ± 8.6 years, 80.5% men). Clinical presentation was stable coronary artery disease in 45 patients (56.2%) and acute coronary syndromes in 33 (43.8%). All the lesions were severely calcified. In addition, 40% were uncrossable lesions, 28.75% were undilatable lesions, 2.5% showed in-stent restenosis, 6.25% showed stent underexpansion, and 7.5% were chronic total occlusions. The combination of ≥ 2 of the above anatomic settings was found in 12.5% of the procedures. The maximum fluence was 73 ± 9.6 mJ/mm2, and the maximum frequency was 72.7 ± 10.4 Hz. The saline flushing technique was initially used in all the procedures, while contrast was used in 2 procedures. The ELCA success and technical success rates were both 91.25%. Adjuvant plaque modification therapies were required in 4 patients. The clinical success rate was 87.5%. ELCA-related complications occurred in 2 procedures (2.5%). After a median follow-up of 15.5 months [IQR, 5.0-29.3], major adverse cardiac events (MACE) (target lesion revascularization, myocardial infarction or cardiac death) occurred in 9 patients (11.25%). Conclusions: Despite the complexity of PCI in severely calcified lesions, ELCA was effective with a relatively low incidence of ELCA-related complications and MACE during follow-up.